2021
DOI: 10.1186/s12889-021-12292-5
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of safety apps for sexualized violence: a narrative scoping review

Abstract: Background Sexualized violence against women is a significant human rights problem worldwide. Safety apps have the capacity to provide women with resources to prevent or respond to experiences of sexualized violence. Methods The aim of the following study was to review the scope of the literature on women’s experiences of safety apps related to sexualized violence. The databases Embase, MEDLINE, PsycINFO, and Scopus were systematically searched, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Most of the literature found on mobile apps focused on health and fitness [3,[17][18][19][20][21][22][23]. There were also some studies on personal safety apps, but most of them either covered a wide age or older demographic, were focused on sexual violence against women, or were focused solely on app development with no associated evaluation [16,[24][25][26][27][28]. Consequently, only 68 articles were eligible for full-text screening.…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
“…Most of the literature found on mobile apps focused on health and fitness [3,[17][18][19][20][21][22][23]. There were also some studies on personal safety apps, but most of them either covered a wide age or older demographic, were focused on sexual violence against women, or were focused solely on app development with no associated evaluation [16,[24][25][26][27][28]. Consequently, only 68 articles were eligible for full-text screening.…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
“…Indeed, one study ultimately excluded East Asia and the Pacific region because of the comparative paucity of apps available for download (Eisenhut et al, 2020: 3). Surveys on research related to women's safety apps has identified that the majority of research has taken place in the United States (Doria et al, 2021). Moreover, most surveys were comprised of college women, only one study reported the sexual orientation of the participants (the sample was almost entirely heterosexual women), and, where ethno-racial makeup was reported, the studies were comprised of a majority Caucasian/White sample group (Doria et al, 2021).…”
Section: Cultural and Geographic Limitationsmentioning
confidence: 99%
“…Nevertheless, studies have identified that using apps provided a great sense of privacy or anonymity than obtaining information from in-person services, and additionally gave users a greater sense of privacy because of the ambiguous/discreet design of the apps in question (Doria et al, 2021). Additionally, the reviewed literature suggested that participants experienced a greater sense of security because the apps helped them avoid judgment/stigma associated with SGBV, which also led to participants having a sense that the apps provided more objective/unbiased help than seeking assistance through friends or family.…”
Section: Security and Privacy Issuesmentioning
confidence: 99%
See 2 more Smart Citations